Blood metabolites and zootechnical parameters in piglets weaned at two ages and with the addition of antimicrobials in the feed - Patiño Fonnegra, Felipe (2019)
The effect of the addition of antimicrobials on zootechnical and metabolic parameters in weaned piglets was evaluated. A total of 150 piglets were used, half weaned at 21 days and the other half at 28 days. Blood samples and weight control were taken on days 1, 15 and 30 post-weaning and daily controls of rectal temperature and occurrence of diarrhoea were recorded. The pigs were fed with a commercial diet and five treatments were used: D1 (basal diet); D2: addition of Zinc Bacitracin; D3: addition of Bacillus subtillis; D4; addition of oregano essential oil, D5: addition of organic acids. A completely random design was used in an arrangement of divided plots (five diets, three repetitions). The animals that consumed the D3 diet (with probiotic) had the best feed conversion ratio, the greatest body weight gain, the lowest severity index of diarrhoea (SID) and the best metabolic parameters (p<0.05), especially in relation to animals in D1 and D2. The weaned animals at 21 days had lower zootechnical indexes, higher ISD and lower metabolic values ​​(p<0.05) compared to animals weaned at 28 days. It is concluded that the addition of B. subtillis and a weaning at 28 days of age showed the best results and this can be an important nutritional alternative to replace antibiotic growth promoters in pig feeding.